2012
DOI: 10.3732/ajb.1100375
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Opuntia s.s. (Cactaceae): Clade delineation, geographic origins, and reticulate evolution

Abstract: Opuntia s.s. is a well-supported clade that includes Nopalea. The clade originated in southwestern SA, but the NA radiation was the most extensive, resulting in broad morphological diversity and frequent species formation through reticulate evolution and polyploidy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
205
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 171 publications
(220 citation statements)
references
References 108 publications
5
205
1
6
Order By: Relevance
“…However, we found no variability in the sequence of this gene in the Mexican Opuntia species studied here. Majure et al (2012b) identified 20 informative characteristics in an 861-bp fragment of the atpB-rbcL region in Opuntia species, but we did not find any polymorphisms in this region with any of the eight enzymes used, suggesting that Mexican accessions conserve the same sequence in this region. It is noteworthy that we also conducted the PCR-RFLP analysis for the ITS region in 70 genotypes and digested with four restriction enzymes (EcoRI, HaeIII, HhaI, and HinfI); however, no polymorphisms were detected among these accessions either (data not shown).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…However, we found no variability in the sequence of this gene in the Mexican Opuntia species studied here. Majure et al (2012b) identified 20 informative characteristics in an 861-bp fragment of the atpB-rbcL region in Opuntia species, but we did not find any polymorphisms in this region with any of the eight enzymes used, suggesting that Mexican accessions conserve the same sequence in this region. It is noteworthy that we also conducted the PCR-RFLP analysis for the ITS region in 70 genotypes and digested with four restriction enzymes (EcoRI, HaeIII, HhaI, and HinfI); however, no polymorphisms were detected among these accessions either (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…However, some problems limit its use in phylogenetic studies, such as frequent indels, microsatellites, inversions, a high degree of homoplasy, and the presence of inversions in the middle of the sequence, which can lead to incorrect alignments; however, psbA-trnH may still be a successful marker due to its high interspecific variability (Korotkova et al, 2011). Korotkova et al (2011) stated that the psbA-trnH spacer is the most successful individual region for operational taxonomic unit identification at the intraspecific level, and the intergenic spacer trnL-trnF has been the most frequently used locus in phylogenetic studies of the Opuntioideae (Griffith and Porter, 2009;Hernández-Hernández et al, 2011;Majure et al, 2012b). ppc and ycf1 have been sequenced in the Opuntieae tribe, and are moderately informative Majure et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations